Sol-gel thin-film based mesoporous silica and carbon nanotubes for the determination of dopamine, uric acid and paracetamol in urine - Canevari, Thiago C. [UNESP]; Raymundo-Pereira, Paulo A. [UNESP]; Landers, Richard; Benvenutti, Edilson V.; Machado, Sergio A. S. [UNESP] (Elsevier B.V., 2013)
This work describes the preparation, characterization and application of a hybrid material composed of disordered mesoporous silica (SiO2) modified with multiwalled carbon nanotubes (MWCNTs), obtained by the sol-gel process using HF as the catalyst. This hybrid material was characterized by N-2 adsorption-desorption isotherms, X-ray powder diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission microscopy (HR-TEM), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). This new hybrid material was used for the construction of a thin film on a glassy carbon electrode. The modified electrode using this material was designated SiO2/MWCNT/GCE. The electrocatalytic properties of the electrode toward dopamine, uric acid and paracetamol oxidation were studied by differential pulse voltammetry. Well-defined and separated oxidation peaks were observed in phosphate buffer solution at pH 7.0, in contrast with the ill-defined peaks observed with unmodified glassy carbon electrodes. The electrode had high sensitivity for the determination of dopamine, uric acid and paracetamol, with the limits of detection obtained using statistical methods, at 0.014, 0.068 and 0.098 mu mol L-1, respectively. The electrode presented some important advantages, including enhanced physical rigidity, surface renewability by polishing and high sensitivity, allowing the simultaneous determination of these three analytes in a human urine sample. Crown Copyright (C) 2013 Published by Elsevier B.V. All rights reserved.
Keywords: Carbon nanotubes; Mesoporous silica; Electrochemical sensor; Dopamine; Uric acid; Paracetamol